Association of exercise participation levels with cardiometabolic health and quality of life in individuals with hepatitis C - Stuart McPherson; Preya Patel; Shion Gosrani; Sarah Hogg; Aaron Wetten; Rachael Welton; Kate Hallsworth; Matthew D Campbell (BMJ Open Gastroenterology)
Objective Hepatitis C virus (HCV) infection is associated with an increased risk of cardiovascular disease (CVD) and reduced health-related quality of life (HRQoL). Although physical activity (PA)/exercise has been shown to reduce CVD risk and improve HRQoL in patients with liver disease, there is limited data in HCV. We aimed to explore the association between PA/exercise levels, CVD risk and HRQoL in patients with HCV and assess individuals’ attitudes to PA/exercise.Design Cross-sectional observational study recruiting consecutive patients with HCV from viral hepatitis clinics. Data were collected on CVD risk factors, anthropometry, HRQoL and the Exercise Benefits and Barriers Scale (EBBS).Results 86 patients were recruited (71% men, 94% white, age 52±13 years); 49% of the cohort self-reported to be currently active. Although HRQoL was reduced across the cohort, patients that were regularly ‘active’ reported significantly higher HRQoL scores across Short-Form 36v2 domains compared with their inactive counterparts (p<0.05). Metabolic and cardiovascular characteristics were no different between groups stratified by PA/exercise status (p>0.05). EBBS scores were similar in the ‘active’ versus ‘inactive’ groups, however, patients categorised as ‘active’ scored significantly higher on the psychological outlook and social interaction subscales (p<0.05) than those that were ‘inactive’. There were significant associations between EBBS scores and HRQoL (p<0.05).Conclusions PA/exercise is associated with increased HRQoL in patients with HCV irrespective of clinical parameters. Addressing specific motivators/barriers to exercise for patients will be key to designing effective PA/exercise interventions in this patient population to ensure maximum uptake and adherence.